Replication Data for "How Much Do Our Neighbors Really Know? The Limits of Community-Based Targeting" - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset contains data and replication code for the study "How Much Do Our Neighbors Really Know? The Limits of Community-Based Targeting," which examines the accuracy and determinants of information used by community members in participatory targeting exercises. The study was conducted in Purworejo Regency, Central Java, Indonesia, using a sample of 300 participants randomly selected across 10 neighborhood units (RTs).